Factors Linked to the Development of Anemia in Pregnant Mothers - Ni Kadek Suantari; Ni Wayan Suarniti; Listina Ade Widya Ningtyas (Media Keperawatan Indonesia, 2024)
Anemia in pregnancy has a high prevalence. This study aims to determine the factors associated with the incidence of anemia in pregnant women at the Klungkung I Community Health Center Regional Technical Implementation Unit. This research uses quantitative methods with a cross-sectional approach. Respondents in this study totaled 36 respondents. The research instrument used a questionnaire and an ANC register book. The data analysis used was univariate and statistical analysis with a significance level of p<0.05. The results of the analysis and univariate analysis were pregnant women with healthy reproduction (69.4%), high education (63.9%), parity of multiparous mothers (77.8%), high economic status (69.4%), frequency of compliance with visits ANC (66.7%), compliance with Fe tablet consumption (69.4%). Bivariate analysis results using the Fisher-exact test on the characteristics of age (0.02), education (0.03), parity (0.01), economic status (0.02), frequency of ANC visits (0.01), and consumption compliance of Fe tablets (0.01). Pregnant women are expected to make ANC visits and consume Fe tablets according to standards so that the health of the mother and fetus remains healthy. Health workers are expected to implement standards for the frequency of ANC visits according to standards and increase education for pregnant women.